Penance of the damned - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2017)
"Ireland, AD 671. King Colgú of Cashel is shocked to learn that his loyal Chief Bishop and advisor has been murdered in the old enemy fortress of the Uí Fidgente. When word reaches Cashel that the culprit will be executed under new law, a larger conflict looms. Dispatched to investigate, Fidelma and her companion Eadulf discover that the man facing punishment is Gormán<U+2014>commander of the King<U+2019>s bodyguard. But Fidelma cannot believe Gormán would carry out such an act<U+2014>and yet he was found locked in a chamber with the body, weapon in hand. The evidence is stacked against him. If they are to exonerate Gormán and keep the peace between the kingdoms, Fidelma and Eadulf must find the true culprit. As the threat of war looms, the date of execution drawers ever closer...